Adaptation and validation of a methdology for determing ammonia flux generated by litter in naturally ventilated poultry houses (2014)
The present work aimed to adapt and validate a precise and simple application method defined as the “Saraz method for the determination of ammonia emissions" (SMDAE), based on the method of mass diffusion, to determine ammonia flux due to mass convection from broiler litter. It was found that ammonia flux (N"A) can be obtained by the SMDAE diffusion method. The SMDAE method presents a recovery efficiency for volatilized ammonia of 77 ± 4% and can be used for ammonia concentrations as high as 0.5 ppm.